Effects of Preoperative Carbohydrate Intake on Inflammatory Markers and Clinical Outcomes in Elderly Patients Undergoing Radical Prostatectomy: A Single-Centre, Double-Blind Randomised Controlled Trial - Hu, Zhen; Liu, Ji; Wang, Fen (Frontiers in Surgery, 2021)
Background: This study aimed to analyse the effects of carbohydrate (CHO) intake on inflammatory markers, comfort and clinical outcomes in elderly patients undergoing open radical prostatectomy. Methods: Patients aged ≥65 years who underwent open radical prostatectomy were randomly divided into CHO, drinking water and fasting groups. A total of 90 patients were enrolled in this study (CHO group, n = 28; placebo group, n = 30 and fasting group, n = 32). Patients in the CHO group were given 800 and 400 ml of carbohydrates 8 hours and 2-3 hours before surgery, respectively. Patients in the placebo group were given 800 and 400 ml of water 8 hours and 2-3 hours before surgery, respectively. Patients in the fasting group did not consume any liquids. The main result is levels of inflammation markers. Secondary results included cellular immunity, comfort, body weight, grip index and clinical results. Results: Compared with the fasting group, the CHO group exhibited a decrease in interleukin 6 (IL-6) levels on days 1 and 7 (75.47 and 7.06 pg/mL, respectively), IL-8 levels on day 1 (274.61 pg/mL) and tumour necrosis factor (TNF) levels on days 1, 3 and 7 (11.16, 9.55 and 9.67 pg/mL, respectively). The placebo group exhibited a decrease in IL-8 (390.26 pg/mL) and TNF levels (13.99 pg/mL) on day 1. Compared with the placebo group, the CHO group exhibited a decrease in IL-6 levels on day 1 and TNF levels on day 3. In the CHO and placebo groups, the thirst and hunger scores decreased on the morning of surgery. Conclusion: Preoperative CHO and drinking water are associated with decreased levels of IL-6, IL-8 and TNF. CHO and water can also reduce thirst and hunger scores. Therefore, we recommend that patients without contraindications should be given 200-400 ml of fluid 2-3 hours before surgery, preferably CHO.